OP0357 Hyperechoic deposits in the renal medulla are associated with severe gout and decreased egfr: a transversal study in 503 vietnamese patients. (12th June 2018) - Bardin, T.; Tran, K.M.; Nguyen, Q.D.; Le, N.H.; Richette, P.; Le Van, P.; Correas, J.-M.; Resche-Rigon, M.
Abstract : Background: Renal medulla crystal deposits have been demonstrated by pathology in severe gout but little studied by ultrasound (US) scan. Objectives: To assess the frequency of hyperechoic renal medulla (HERM) in gouty patients and factors associated with their development. Methods: Renal US scan using a Ecube 9 echograph (Alpinion S. Korea), was performed in gout patients (ACR/EULAR criteria) consecutively seen at the Vien Gut general clinic, Ho Chi Minh City, Vietnam, and receiving no ULT at presentation. Age and sex of patients, gout features, associated diseases, serum (S) uric acid (UA), eGFR (MDRD), urinary lab stick parameters, urine UA/creatinine ratio, and fractional clearance of urate (FCU) were recorded. Patients with HERM were counted and compared with those who had no medullary deposits by the Wilcoxon rank sum test for continuous varables and the Fischer exact test for categorical variables. Multivariable logistic model was used to assess relation between variables at inclusion in the study and presence of medulla deposits. Results: 503 consecutive patients (500 males) were included. They had a median age of 46 years, median BMI of 25 kg/m2, median gout duration of 4 years. 280 (56%) had clinical tophi, 154 (31%) urate arthropathy, 28; 5 6%) urolithiasis, 112 (22%) hypertension, 58 (11.5%) type 2 diabetes, 5 (1%) coronary heart disease. Their median eGFR was 78 ml/min, SUA 423 micromol/L, FCU 0.063, urine UA/creatinine ratio 0.253, urinary pH 6. Diffuse and bilateral HERM on the B mode with frequent twinkling artefacts on the Doppler mode was identified in 181 (36%) of the 503 patients. Univariate analysis showed that HERM associated with higher age, longer duration of gout, clinical tophi, urate arthropathy (p<0.0001 for each of the variables), higher uricemia (p=0.001), hypertension (p=0.0008), CHD (p=0.0006), lower eGFR (p<0.0001), leucocyturia (p=0.02), proteinuria (p=0.02). No association with US-diagnosed urolithiasis, hematuria, urine UA/creatinine ratio, FCU and urinary pH was found. In multivariate analysis, log of the duration of gout (0R: 2.22 (CI: 1.63–3.08), p<0.001), clinical tophi (OR: 8.21 (4.23–16.91) p<0.001), urate arthropathy (OR: 3.74 (2.18–6.52, p<0.001), and lower eGFR (OR: 0.86 (0.75–0.99) for each 10 ml/min decrease, p=0.04) were significantly associated with HERM. Conclusions: In our gout population, HERM was observed in 36% of patients, correlated with decreased renal function, and clearly associated with severe gout, but not with features of uric acic lithiasis. Disclosure of Interest: T. Bardin Consultant for: Grunnenthal, Ipsen Menarini, Astrazeneca, NovartisSobi, K. M. Tran: None declared, Q. D. Nguyen: None declared, N. H. Le : None declared, P. Richette Consultant for: Grunnenthal, Ipsen Menarini, Astrazeneca, NovartisSobi, P. Le Van: None declared, J.-M. Correas: None declared, M. Resche-Rigon: None declared